PRIORITIES, CONCERNS AND REGRET AMONG HEAD AND NECK CANCER PATIENTS - Windon, Melina J. (Cancer, 2019)
BACKGROUND: In the era of deintensification, little data is available regarding patients’ treatment preferences. This study evaluates treatment-related priorities, concerns and regret among head and neck squamous cell cancer (HNSCC) patients. METHODS: Patients with HNSCC (n=150) ranked the importance of ten non-oncologic treatment goals, relative to the oncologic goals cure and survival. Level of concern regarding 11 issues and decision regret was recorded. Median rank was reported overall, and factors associated with odds of rank as a top three priority were modeled using logistic regression. RESULTS: Among the treatment effects analyzed, odds of being a top three priority was especially high for cure (odds 9.17, 95% CI 5.05–16.63), followed by survival and swallow (1.26, 95% CI 0.88–1.80 and 0.85, 95% CI 0.59–1.21, respectively). Prioritization of cure, survival and swallow was similar by human papillomavirus (HPV) tumor status. By increasing decade of age, older participants were significantly less likely than younger to prioritize survival (odds ratio, 0.72; 95%CI, 0.52–1.00). Concern regarding mortality (p=0.04) and transmission of HPV to spouse (p=0.03) was more frequent among participants with HPV-HNSCC. Regret increased with additional treatment modalities (p=0.02). CONCLUSIONS: HNSCC patients overwhelming prioritize cure, followed by survival and swallow. The decreased prioritization of survival by older age supports further examination of treatment preference by age. The precedence of oncologic over non-oncologic priorities among patients regardless of HPV tumor status supports a conservative adoption of deintensification regimens until the interplay between competing oncologic and non-oncologic treatment goals is better understood.